Design Phase Constructability Improvement Strategies For Highway Projects In Uganda - Alinaitwe, Henry; Nyamutale, William; Tindiwensi, Dan (Penerbit Universiti Sains Malaysia, 2014)
There is great concern regarding the escalation of project costs and delayed completion of road work in Uganda. This has been partly associated with a lack of constructability. Studies have demonstrated that improved constructability leads to significant improvements in project cost savings and reduced completion times. The main aim of this study was to establish design phase constructability improvement strategies for highway projects in Uganda. A pragmatic approach of both qualitative and quantitative research methods was used for this study. Concepts of constructability were identified and rated. Using factor analysis, major design phase constructability improvement recommendations were identified. These factors include conducting formal constructability reviews; ensuring adequate materials design, communication, coordination and scheduling; analysing jobsite accessibility and storage requirements; engaging experienced personnel and adopting Computer Aided Design (CAD); ensuring thorough site investigation and clear design information; and developing designs that are sensitive to safety and weather conditions. The primary recommendation is to include constructability reviews to form part of the formal design process, using a separate team of construction experts (consultants) that are distinct from the design consultant before the construction stage of the project.